2021
DOI: 10.1021/acs.est.1c00862
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Trihalomethane Concentrations with Risk of All-Cause and Cause-Specific Mortality in U.S. Adults: A Prospective Cohort Study

Abstract: Water chlorination can lead to the formation of disinfection byproducts, including trihalomethanes (THMs). However, few epidemiologic studies have explored associations between THM exposure and mortality. This study included 6720 adults aged ≥40 years from the National Health and Nutrition Examination Survey 1999−2012 who had blood THM concentrations quantified. A higher risk of all-cause mortality was found across increasing quartile concentrations of blood chloroform (TCM) and total THMs (TTHMs; sum of all f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…Chloroform is the most prevalent biomarker of DBPs which can be absorbed through ingestion, inhalation, and dermal contact (73). A prospective cohort study revealed a positive relationship between total brominated THMs, including Br-THMs, the sum of (BDCM, DBCM, and TBM) and TTHM concentrations, and the risk of cancer death (74). Some studies showed that long-term chloroform exposures are linked to colorectal cancer and bladder cancer (75, 76).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroform is the most prevalent biomarker of DBPs which can be absorbed through ingestion, inhalation, and dermal contact (73). A prospective cohort study revealed a positive relationship between total brominated THMs, including Br-THMs, the sum of (BDCM, DBCM, and TBM) and TTHM concentrations, and the risk of cancer death (74). Some studies showed that long-term chloroform exposures are linked to colorectal cancer and bladder cancer (75, 76).…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for peripheral blood and tap water collection, sampling, and determination have been described in previous studies. ,, Briefly, a single blood and household water sample was collected during the examination. The concentrations of chloroform (TCM), bromodichloromethane (BDCM), dibromochloromethane (DBCM), and bromoform (TBM) in blood and tap water were measured via solid-phase microextraction gas chromatography and mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Disinfection byproducts (DBPs) are a class of contaminants indirectly generated during the process of water disinfection, through the reaction of chemical disinfectants (e.g., chlorine) with organic matter in raw water . Humans are ubiquitously exposed to DBPs through various water-use activities such as drinking water, showering or bathing, and swimming .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age was classified to 2 groups: <65 years old (non-elderly) and ≥ 65 years old (elderly). Gender was categorized into “male” and “female.” The race was assigned to 4 groups: Mexican American, non-Hispanic white, non-Hispanic black, and others ( 17 ). Physical activity was defined as “inactive” or “active” according to the average physical activity time (“active” was defined as getting more than 75 min/week vigorous or 150 min/week moderate physical activity) ( 18 ).…”
Section: Methodsmentioning
confidence: 99%